The good, the bad and the ugly of South African fatal road accidents - Verster, Tanja; Fourie, Erika (South African Journal of Science, 2018)
We reflect on the good, the bad and the ugly of the fatal accidents occurring on South Africa’s roads. The cost of human lives indisputably equates to ‘the ugly’ and the economic cost of accidents associates with ‘the bad’. ‘The good’ relates to the reduction of both these costs that may result from the entrance of self-driving cars into the South African market as well as awareness campaigns like the Arrive Alive National Road Safety Strategy. The general contribution of this paper is to raise awareness of the effects of accidents, more specifically fatal accidents. Current trends in terms of human factors as well as road and environmental factors involved in the fatal accidents on South African roads are summarised. This paper also serves as a preliminary investigation into possible factors influencing these accidents, which ought to be of interest to a very broad readership, more specifically those focusing on risk analysis, and certainly is of interest to any citizen of South Africa. Significance: • Awareness is raised of the effects of fatal accidents on South African roads. • Current trends in terms of human factors as well as road and environmental factors on road accidents are reflected upon. • The futuristic effect of self-driving cars is explored.